EXPERIMENTAL STUDIES OF WALL GIRDERS IN DIFFERENT TYPES OF BRIDGE DECK - Zakora, O. L.; Lynnyk, H. O.; Marochka, V. V. (Science and Transport Progress, 2010)
The results of experimental studies of wall girders under live load are given in the paper. These studies were conducted in several stages with different types of the bridge floor.